Presence and site-matching of ischemia at stress-scintigraphy or contrast stress-echo in individuals developing myocardial infarction within 3 months: does stenosis severity matter? - Siniscalchi, Carmine; Reverberi, Claudio; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: Individuals with ischemia during cardiac stress-test (cST) have a high risk of developing myocardial infarction (MI), but the pathophysiologic mechanism has never been clarified. It is thought that non flow-limiting coronary plaques (FLP) cause more often MI than FLP, but this is in contradiction with the predictive value of cST. We investigated the correspondence between reversible ischemia and location of subsequent MI, since functional assessment shortly before MI could clarify whether the culprit plaque is a FLP or not. Methods: From 4505 MI and 4959 cST -2017 contrast perfusion stress-echo (cDipSE) and 2942 scintigraphy (SPECT)- performed from 2007 to 2011- 25 patients fulfilling criteria (